Cloning and analysis of ermG, a new macrolide-lincosamide-streptogramin B resistance element from Bacillus sphaericus. - Monod, M (1987)
To analyze the regulation of a newly discovered macrolide-lincosamide-streptogramin B resistance element (ermG) found in a soil isolate of Bacillus sphaericus, we cloned this determinant and obtained its DNA sequence. Minicell analysis revealed that ermG specifies a 29,000-dalton protein, the synthesis of which is induced by erythromycin. S1 nuclease mapping was used to identify the transcriptional start site. These experiments demonstrated the presence on the ermG mRNA of a 197 to 198-base leader. Within the leader are two small open reading frames (ORFs) capable of encoding 11- and 19-amino-acid peptides. Each ORF is preceded by a suitably spaced Shine-Dalgarno sequence. The ermG protein is encoded by a large ORF that encodes a 244-amino-acid protein, in agreement with the minicell results. This protein and the 19-amino-acid peptide are highly homologous to the equivalent products of ermC and ermA. We conclude, on the basis of this homology, that ermG encodes an rRNA transmethylase. The leader of ermG can be folded into a structure that sequesters the Shine-Dalgarno sequence and start codon for the large ORF (SD3). On the basis of these data and on the observed greater responsiveness of the ermG system than of the ermC system to low concentrations of erythromycin, we propose a model for the regulation of this gene in which the stalling of a ribosome under the influence of an inducer, while reading either peptide, suffices to uncover SD3 and allow translation of the rRNA transmethylase. The evolution of ermG is discussed.